Cytoplasmic DNA and AIM2 inflammasome in RA: where they come from and where they go? - Xu, Conghui; Jing, Weiyao; Liu, Cui; Yuan, Bo; Zhang, Xinghua; Liu, Limei; Zhang, Fengfan; Chen, Ping; Liu, Qiang; Wang, Haidong; Du, Xiaozheng (Frontiers in Immunology, 2024)
Rheumatoid arthritis is a chronic autoimmune disease of undetermined etiology characterized by symmetric synovitis with predominantly destructive and multiple joint inflammation. Cytoplasmic DNA sensors that recognize protein molecules that are not themselves or abnormal dsDNA fragments play an integral role in the generation and perpetuation of autoimmune diseases by activating different signaling pathways and triggering innate immune signaling pathways and host defenses. Among them, melanoma deficiency factor 2 (AIM2) recognizes damaged DNA and double-stranded DNA and binds to them to further assemble inflammasome, initiating the innate immune response and participating in the pathophysiological process of rheumatoid arthritis. In this article, we review the research progress on the source of cytoplasmic DNA, the mechanism of assembly and activation of AIM2 inflammasome, and the related roles of other cytoplasmic DNA sensors in rheumatoid arthritis.